2013
DOI: 10.1016/j.ijhydene.2012.12.082
|View full text |Cite
|
Sign up to set email alerts
|

Critical radius for hot-jet ignition of hydrogen–air mixtures

Abstract: a b s t r a c tThis study addresses deflagration initiation of lean and stoichiometric hydrogeneair mixtures by the sudden discharge of a hot jet of their adiabatic combustion products. The objective is to compute the minimum jet radius required for ignition, a relevant quantity of interest for safety and technological applications. For sufficiently small discharge velocities, the numerical solution of the problem requires integration of the axisymmetric NaviereStokes equations for chemically reacting ideal-ga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(18 citation statements)
references
References 20 publications
(22 reference statements)
1
17
0
Order By: Relevance
“…It is indicated that at this point the detonation is at the attenuation stage. On the other hand, the Mach stem gradually becomes longer from the wall boundary to 16 the center of the flowfield, suggesting that the reflection of slapping waves on the side walls gradually reaches the center of the flowfield. Finally in Fig.13(d) a new collision in the center of the flowfield is formed and results in the generation of a small bump shown by the blue circle.…”
Section: Cj Detonationmentioning
confidence: 99%
See 1 more Smart Citation
“…It is indicated that at this point the detonation is at the attenuation stage. On the other hand, the Mach stem gradually becomes longer from the wall boundary to 16 the center of the flowfield, suggesting that the reflection of slapping waves on the side walls gradually reaches the center of the flowfield. Finally in Fig.13(d) a new collision in the center of the flowfield is formed and results in the generation of a small bump shown by the blue circle.…”
Section: Cj Detonationmentioning
confidence: 99%
“…Except for direct initiation [6][7][8][9] which can realize initiation immediately but need large energy, an alternative is to use a hot jet that can also realize quick initiation [10] . Researches on detonation initiation with a hot jet have been numerously investigated [11][12][13][14][15][16] , but most of them are carried out only in quiescent combustible mixtures. Detonation initiation and propagation using a hot jet were conducted experimentally by Ishii et al [17] , where the Mach numbers of combustible mixtures were 0.9 and 1.2.…”
Section: Introductionmentioning
confidence: 99%
“…An alternative approach is the utilization of a hot jet which can also ignite detonation initiation very fast [8] , because the flame acceleration process of deflagration to detonation transition (DDT) is bypassed essentially. The hot jet initiation has been investigated comprehensively in quiescent combustible mixtures [9][10][11][12] , but in supersonic combustible mixtures only a few experimental researches have been carried out [13][14][15] . Ishii et al [13] conducted experiments in combustible mixtures whose Mach numbers were 0.9 and 1.2 to investigate detonations using a hot jet initiation.…”
Section: Introductionmentioning
confidence: 99%
“…gas impinges through a narrow nozzle into a quiescent hydrogen/air mixture due to an explosion in another chamber. More recently, numerical investigations were carried out by Iglesias et al [7] and Carpio et al [8] for hot jets. [8] investigated the minimum jet radius of the nozzle required to ignite the surrounding hydrogen/air mixture.…”
Section: Introductionmentioning
confidence: 99%
“…More recently, numerical investigations were carried out by Iglesias et al [7] and Carpio et al [8] for hot jets. [8] investigated the minimum jet radius of the nozzle required to ignite the surrounding hydrogen/air mixture. The impact of turbulence and mixing on the autoignition of non-premixed fuel, released from a nozzle into a turbulent hot co-flow of air in a pipe, was investigated experimentally by Markides and Mastorakos [9].…”
Section: Introductionmentioning
confidence: 99%